Analisis Yuridis Pemanfaatan Aset Kripto untuk Kepentingan Investasi dan Transaksi di Indonesia - Widi Nugrahaningsih; Novemy Triyandari Nugroho (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Digital currencies can now be utilized by people in various countries, including Indonesia. The Commodity Futures Trading Supervisory Agency (Bappebti) noted that as of November 2023, the number of registered crypto asset customers reached 18.25 million. Every month it has a growth of 437.9 thousand customers calculated since February 2021. The problem in the study, how is the use of crypto assets in Indonesia for investment and transaction purposes in Indonesia.The purpose of the study, to analyze the use of crypto assets in Indonesia for investment and transaction purposes in Indonesia. This research is normative juridical, legal material collection techniques using library research. Data analysis technique, by collecting data, analyzing data, followed by drawing conclusions. Every transaction uses a currency benchmark. The definition of currency is money issued by the Unitary State of the Republic of Indonesia, hereinafter referred to as Rupiah. It is money that is a legal tender. Article 2 of Bappebti Regulation No.5 of 2019 concerning Technical Provisions for the Implementation of the Crypto Asset Physical Market on futures exchanges, crypto asset trading must be based on legal certainty. Conclusion, that crypto assets in Indonesia can be used as a means of investment for the community. with provisions in accordance with the Minister of Trade Regulation Number 99 of 2018. Buying and selling crypto can only be done on the futures exchange.